Factors Affecting The Performance Of Auditors During Pandemic Companies In Hospital Services In The City Of Sibolga - Hendra Saputra; Ayu Kurnia Sari; Ku Halim Bin Ku Arifin; Aulia Aulia (International Journal of Social Service and Research, 2022)
Many factors influence the auditor in carrying out his duties to make auditor judgment. One of the factors that influence an auditor's decision is the individual behavior aspect of the auditor. Well-known audit research bodies have demonstrated that a number of individual-level factors have been shown to influence an auditor's decision. Many studies related to the behavior of individual auditors have also been carried out.